Fouling formation and thermal performance of aqueous carbon nanotube nanofluid in a heat sink with rectangular parallel microchannel. (August 2017) - Sarafraz, M.M.; Nikkhah, V.; Nakhjavani, M.; Arya, A.
Highlights: Experimental investigation on thermal performance of microchannel heat sink. Aqueous CNT nanofluids at wt.% = 0.05–0.1 were used as the coolant. Lower temperature profile and higher HTC were recorded for nanofluids. Fouling thermal resistance showed an asymptotic behavior over the time. Abstract: Experimental investigation is performed on the thermal performance of a copper-made heat sink with rectangular microchannel. Carbon nano tube aqueous nanofluid is used as a coolant inside the microchannel at mass concentrations of 0.05–0.1%. Influence of different operating parameters including applied heat flux, fluid flow rate and mass concentration of nanofluid on the local and average heat transfer coefficients, fouling thermal resistance, overall thermal resistance and local (axial) temperature profile is investigated. Results showed the higher heat transfer coefficient and lower temperature profile inside the heat sink in comparison with the base fluid (water). Fluid flow rate and mass concentrations were found to increase the heat transfer coefficient significantly, while slight improvement was seen when higher heat fluxes were applied into the microchannel heat sink. Fouling thermal resistance was found to asymptotically increase with an increase in operating time and strongly depends on the concentration of nanofluid such that the required operating time to reach a constant value was different. The higher the mass concentration, the lower operating time is required to reach the constant fouling thermal resistance. However, overall thermal resistance of the microchannel (without considering the fouling effect) was found to linearly decrease with the mass concentration of nanofluid.